Maternal Conjugated Linoleic Acid Supply in Combination With or Without Essential Fatty Acids During Late Pregnancy and Early Lactation: Investigations on Physico-Chemical Characteristics of the Jejunal Content and Jejunal Microbiota in Neonatal Calves - Liermann, Wendy; Wissing, Katrin Lena; Reyer, Henry; Trakooljul, Nares; Dannenberger, Dirk; Tröscher, Arnulf; Hammon, Harald Michael (Frontiers in Veterinary Science, 2022)
Conjugated linoleic acids (CLAs) modulate the fatty acid composition in dairy cow milk, which represents the most important nutrient source of neonatal calves. In turn, dietary fatty acids are known to influence the gut microbiota. The current preliminary study investigated effects of a maternal fatty acid supplementation (MFAS) during transition period with coconut oil (CON, control), CLA (Lutalin®) or CLA+EFA (Lutalin® + essential fatty acids - linseed oil; safflower oil) on physico-chemical characteristics of jejunal content and microbiota of 5 day-old calves. MFAS of CLA+EFA increased α-linolenic, eicosapentaenoic, docosapentaenoic, and n-3 fatty acid proportions in jejunum compared to the other groups (P < 0.05). Proportions of n-6 and polyunsaturated fatty acids increased by MFAS of CLA+EFA compared to CON (P < 0.05). Most abundant phyla in the jejunum were Proteobacteria, Firmicutes and Bacteroidota. CLA+EFA decreased the relative abundance of Diplorickettsiales (Proteobacteria) compared to CON and CLA (P < 0.05). CLA calves showed a lower abundance of Enterobacterales (Proteobacteria) compared to CON calves (P = 0.001). The abundance of Veillonellales-Selenomonadales and RF39 (Firmicutes) decreased in CLA+EFA calves compared to CON calves (P < 0.05). Bacteroidales (Bacteroidota) decreased in CLA+EFA calves compared to CLA calves (P < 0.05). The relative abundance of Cyanobacteria and Euryarchaeota decreased and the abundance of Chloroflexi increased in CLA+EFA calves compared to CON and CLA calves (P < 0.05). MFAS alters the fatty acid composition and microbial milieu in the intestinal content of neonatal calves due to their ability to modulate colostral fatty acid composition of dams.